Enablers of psychosocial recovery in pediatric burns: perspectives from the children, parents and burn recovery support staff - Ashley Van Niekerk; Roxanne Jacobs; Nancy Hornsby; Robyn Singh-Adriaanse; Mathilde Sengoelge; Lucie Laflamme (BMC, 2020)
Abstract Background Pediatric burn injuries are a major cause of death and injury, occurring mainly in resource poor environments. Recovery from burns is widely reported to be constrained by physical, psychological, relationship and reintegration challenges. These challenges have been widely described, but not the enablers of psychosocial recovery. This is especially true in pediatric burn research, with few multi- perspective studies on the recovery process. Methods This qualitative study involved 8 focus group discussions (four with 15 children post-burn injury, four with 15 caregivers) and 12 individual interviews with staff working in pediatric burns that explored the psychosocial needs of children after a burn and the enablers of their recovery. Purposive sampling was utilized and recruitment of all three categories of participants was done primarily through the only hospital burns unit in the Western Cape, South Africa. The interviews focused on factors that supported the child's recovery and were sequentially facilitated from the child and the family's experiences during hospitalization, to the return home to family and friends, followed by re-entry into school. Thematic analysis was used to analyze verbatim interview transcripts. Results The recovery enablers that emerged included: (i) Presence and reassurance; indicating the comfort and practical help provided by family and close friends in the hospital and throughout the recovery process; (ii) Normalizing interactions and acceptance; where children were treated the same as before the injury to promote the acceptance of self and by others especially once the child returned home; and (iii) Sensitization of others and protection; signifying how persons around the child had assisted the children to deal with issues in the reintegration process including the re-entry to school. Conclusions This study indicates that the psychosocial recovery process of children hospitalized for burns is enabled by the supportive relationships from family members, close friends and burn staff, present during hospitalization, the return home, and school re-entry. Support included comfort and physical presence of trusted others and emotional support; affirmation of the child's identity and belonging despite appearance changes; and the advocacy and protection for the re-entry back into the school, and more generally the community.